Culture-creating activities in the city space: examples from Lodz. Anthropological contexts - Karpińska, Grażyna Ewa (Instytut Archeologii i Etnologii PAN, 2020)
Space not only provides a frame, or an arena, for human life, but it is also an important factor of change and an effect of the society’s organisation. This is one of the reasons why grassroots culture-creating activities aimed at marking human presence in a certain place, and altering the perception of space, materialise there. In the article, I present examples of culture-creating practices addressed to the residents of two streets in Lodz; streets which are relatively isolated in terms of space and social contexts and which have been categorised by sociologists as an enclave of poverty. I describe actions by the performance artist Agnieszka Ziemiszewska and the circle of culture animators centring on the “White Crows” Foundation for the Living Culture [Fundacja na rzecz Kultury Żywej “Białe Gawrony”], treating them as means to recognise the context and character of grassroots culture-creating practices aimed a reformatting the socio-cultural identity of a particular area of a city
24 cm
Keywords: city space; grassroots culture-creating practices; performativism; intervention projects; socialisation projects; discovering local resources; Lodz; Poland